STUDI KOMUNITAS RUMPUT LAUT PADA BERBAGAI SUBSTRAT DI PERAIRAN PANTAI PERMISAN KABUPATEN CILACAP - Eti Ferawati; Dwi Sunu Widyartini; Ilalqisny Insan (Scripta Biologica, 2014)
Seaweed naturally grows in substrate of sand, mixing between sand, mud and shell fragments, and also coral. Previous researches stated that there were types of seaweed that able to grow in more than one substrates. The aims of this research was to know the community structure such as diversity, domination, evenness, and similarity of seaweed on various substrates in Permisan beach, Central java. This research used survey method and samples were randomly selected for each substrate with quadrate of 1 x 1 m2. The research found that 20 kinds of seaweeds with biomass for about 4,669 g. Seven kinds of seaweed that grow in sand substrate with biomass for about 0,636 g, 20 kinds of seaweed in coral substrate with biomass for about 2,399 g, and 12 kinds of seaweeds in mixing substrate with biomass for about 1,634 g. Diversity index value in Permisan beach was ranging between 0,064-0,828 and categorized as low. Domination index value was ranging between 0,213-1,193, which means there was dominating variety. Evenness index value was ranging between 0,021-0,276, which means the community was unstable. The highest similarity index value was coral substrate-mixing for about 75%.